2014
DOI: 10.1103/physreve.90.042602
|View full text |Cite
|
Sign up to set email alerts
|

Pulling-force-induced elongation and alignment effects on entanglement and knotting characteristics of linear polymers in a melt

Abstract: We employ a primitive path (PP) algorithm and the Gauss linking integral to study the degree of entanglement and knotting characteristics of linear polymer model chains in a melt under the action of a constant pulling force applied to selected chain ends. Our results for the amount of entanglement, the linking number, the average crossing number, the writhe of the chains and their PPs and the writhe of the entanglement strands all suggest a different response at the length scale of entanglement strands than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 89 publications
0
30
0
Order By: Relevance
“…Specifically, a measure of entanglement that can be directly applied to open chains and is a continuous function of the chain coordinates is the Gauss linking integral. This measure has been successfully applied to polymers in order to study polymer entanglement and it has been shown that it correlates with the physical properties of polymeric material [19][20][21][22]. The Gauss linking integral has likewise been used to classify protein conformations successfully [3,25] and it was shown that the maximum linking between any two parts of a protein correlates with its folding rate [4].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a measure of entanglement that can be directly applied to open chains and is a continuous function of the chain coordinates is the Gauss linking integral. This measure has been successfully applied to polymers in order to study polymer entanglement and it has been shown that it correlates with the physical properties of polymeric material [19][20][21][22]. The Gauss linking integral has likewise been used to classify protein conformations successfully [3,25] and it was shown that the maximum linking between any two parts of a protein correlates with its folding rate [4].…”
Section: Introductionmentioning
confidence: 99%
“…The number of kinks has been shown to increase with viscosity [9,10]. A similar inverse behavior between the Writhe of the chains and the number of kinks was observed in the initial time of an elongation of the chains [37].…”
Section: Bulk Mechanical Responsesmentioning
confidence: 68%
“…In non-equilibrium conditions, the relation becomes more complex [37]. The viscosity can be obtained as the limit η=limω0G2(ω)/ω.…”
Section: Bulk Mechanical Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Exactly the same considerations apply for the linking number and the self-linking number. Indeed, computer experiments indicate that the linking number and the writhe are effective indirect measures of whatever one might call "entanglement", especially in systems of "random" filaments [41,27,43,44,45,46,47,48,42,49,50,51,52,53,54] and it has been shown that they can provide information relevant to the tube model [52,53].…”
Section: Introductionmentioning
confidence: 98%